Genomics-Guided Drawing of Molecular and Pathophysiological Components of Malignant Regulatory Signatures Reveals a Pivotal Role in Human Diseases of Stem Cell-Associated Retroviral Sequences and Functionally-Active hESC Enhancers - Glinsky, Gennadi V. (Frontiers in Oncology, 2021)
Repetitive DNA sequences (repeats) colonized two-third of human genomes and a majority of repeats comprised of transposable genetic elements (TE). Evolutionary distinct categories of TE represent nucleic acid sequences that are repeatedly copied from and pasted into chromosomes at multiple genomic locations and acquired a multitude of regulatory functions. Here, genomics-guided maps of stemness regulatory signatures were drawn to dissect the contribution of TE to clinical manifestations of malignant phenotypes of human cancers. From patients’ and physicians’ perspectives, the clinical definition of a tumor’s malignant phenotype could be restricted to the early diagnosis of sub-types of malignancies with the increased risk of therapy failure and high likelihood of death from cancer. It is the viewpoint from which the understanding of stemness and malignant regulatory signatures is considered in this contribution. Genomics-guided analyses of experimental and clinical observations revealed the pivotal role of human stem cell-associated retroviral sequences (SCARS) in the origin and pathophysiology of clinically-lethal malignancies. SCARS were defined as the evolutionary- and biologically-related family of genomic regulatory sequences, the principal physiological function of which is to create and maintain the stemness phenotype during human preimplantation embryogenesis. For cell differentiation to occur, SCARS expression must be silenced and SCARS activity remains repressed in most terminally-differentiated human cells which are destined to perform specialized functions in the human body. Epigenetic reprogramming, de-repression, and sustained activity of SCARS results in various differentiation-defective phenotypes. One of most prominent tissue- and organ-specific clinical manifestations of sustained SCARS activities is diagnosed as a pathological condition defined by consensus of morphological, molecular, and genetic examinations as the malignant growth. Here, contemporary evidence are acquired, analyzed, and reported defining both novel diagnostic tools and druggable molecular targets readily amenable for diagnosis and efficient therapeutic management of clinically-lethal malignancies. These diagnostic and therapeutic approaches are based on monitoring of high-fidelity molecular signals of continuing SCARS activities in conjunction with genomic regulatory networks of thousands’ functionally-active embryonic enhancers affecting down-stream phenotype-altering genetic loci. Reported herein observations support a model of SCARS-activation triggered singular source code facilitating the intracellular propagation and intercellular (systemic) dissemination of disease states in human body.